Diurnal Air Quality Monitoring in Khumaltar Area, Lalitpur, Nepal - Shrestha, Sujen Man; Thapa, Kanchan; Joshi, Tista Prasai (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Air pollution is becoming a serious matter of concern from different aspects of our lives. It adversely affects the well being of the individuals or cause damages to properties. Pollutants identification requires measurements by standard methods of sampling and analysis. In this study, monitoring of TSP, PM10, SO2 and NO2 were performed during the months of April – August, 2008 by using high volume sampler, i. e. Envirotech APM 451 Model. Four hours (11:00 am to 3:00 pm) of monitoring for SO2 and NO2 , 24 hours of monitoring for TSP and PM10 were carried out. SO2 concentration ranged from 4.8 ?g/m3 to 20.5 ?g/m3 and NO2 concentration ranged from 1.2 ?g/m3 to 8.8 ?g/m3 for four hour monitoring period. TSP concentration ranged from 24.7 ?g/m3 to 82.0 ?g/m3 whereas PM10 concentration ranged from 25.4 ?g/m3 to 152.4 ?g/m3 for 24 hours of monitoring. Present study concluded that the air quality of Khumaltar area in Lalitpur, Nepal met WHO as well as NAAQS standards during the study period. Nepalese cities/towns have always been thought to be serious in terms of particulate matter pollution but consideration of the trend of gasesous pollutants emitted from vehicle exhaust is recommended for future research. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015